Gambaran Perubahan Hemodinamik Post Anestesi Spinal Dan General Anestesi - Soamole, Muhammad Zulhaq Nurul Aqsha; Wibowo, Tophan Heri; Khasanah, Suci (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background : Anesthesia has an emphasis and potentiation effect related to its relative strength and quality. For surgery in Indonesia, it has been recorded with a percentage of 12.8% (Firdaus, 2022). In connection with surgical procedures, one of the most necessary actions is anesthesia. Anesthesia techniques are broadly divided into two types, namely general anesthesia and regional anesthesia (spinal anesthesia). The act of anesthesia also has its own advantages and disadvantages, one of which is the change in hemodynamics that occurs in patients who have been given anesthesia. The factors that can affect hemodynamics such as comorbidities, the status of the American Society of Anesthesiologists (ASA) and the length of surgery. Method : This research is in the category of quantitative research with a type of research that uses descriptive observation techniques. The approach used during the study is cross sectional, which is a research by learning a simple dynamic technique with an observation approach that is carried out only once. Results : Based on the study, it was found that patients who had been given anesthesia often experienced significant hemodynamic changes